Suspended lead suit and physician radiation doses during coronary angiography. Issue 4 (30th December 2021) - Salcido‐Rios, Jose; McNamara, David A.; VanOosterhout, Stacie; VanLoo, Lisa; Redmond, Meaghan; Parker, Jessica L.; Madder, Ryan D.
Abstract: Objective: This study was performed to evaluate physician radiation doses with the use of a suspended lead suit. Background: Interventional cardiologists face substantial occupational risks from chronic radiation exposure and wearing heavy lead aprons. Methods: Head‐level physician radiation doses, collected using real‐time dosimeters during consecutive coronary angiography procedures, were compared with the use of a suspended lead suit versus conventional lead aprons. Multiple linear regression analyses were completed using physician radiation doses as the response and testing patient variables (body mass index, age, sex), procedural variables (right heart catheterization, fractional flow reserve, percutaneous coronary intervention, radial access), and shielding variables (radiation‐absorbing pad, accessory lead shield, suspended lead suit) as the predictors. Results: Among 1054 coronary angiography procedures, 691 (65.6%) were performed with a suspended lead suit and 363 (34.4%) with lead aprons. There was no significant difference in dose area product between groups (61.7 [41.0, 94.9] mGy·cm 2 vs. 64.6 [42.9, 96.9] mGy·cm 2, p  = 0.20). Median head‐level physician radiation doses were 10.2 [3.2, 35.5] μSv with lead aprons and 0.2 [0.1, 0.9] μSv with a suspended lead suit ( p  < 0.001), representing a 98.0% reduced dose with suspended lead. In the fully adjusted regression model, the use of a suspended lead suit was independently associated with a 93.8% reduction (95% confidence interval: −95.0, −92.3; p  < 0.001) in physician radiation dose. Conclusion: Compared to conventional lead aprons, the use of a suspended lead suit during coronary angiography was associated with marked reductions in head‐level physician radiation doses.